ISSUES OF SHORTENED INQUEST PROCEDURE IN THE RUSSIAN CRIMINAL PROCEDURE - A. A. Yunusov; R. R. Safin (Russian Journal of Economics and Law)
Objective: the reveal and characterize the problem situations in the sphere of normative regulation of shortened inquest institution and practice of its implementation in the Russian criminal procedure. Methods: dialectic-materialistic cognition method and general scientific, special and particular scientific research methods. Results: it is theoretically proved that the shortened inquest institution is imperfect, inefficient and need drastic changes of normative character; the criteria of simplifies procedures implementation for every particular crime should be the level of public threat of the crimes; it is necessary to limit the complainant’s rights when solving the question of shortened inquest procedure implementation; the law-enforcement body cannot objective observe the time of shortened inquest procedure stipulated by the law. Scientific novelty: the authors were among the first in the Russian criminal-procedural doctrine to reveal the problems of the new criminal-procedural institution of shortened inquest, which are of theoretical-application and normative character. Practical significance: orientation to improving the preliminary inquest. The research results can be used to improve the criminal-procedural legislation, as well as to increase the efficiency of the corresponding type of practical activity.